2009
DOI: 10.1161/circulationaha.108.765701
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function Predicts Progression of Carotid Intima-Media Thickness

Abstract: Background-Endothelial dysfunction develops early and has been shown to predict the development of clinical complications of atherosclerosis. However, the relationship between early endothelial dysfunction and the progression of arterial disease in the general population is unknown. We investigated endothelial dysfunction, risk factors, and progression of carotid intima-media thickness (cIMT) in late- Further adjustment for waist circumference, triglycerides, and employment grade had no significant effect. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
205
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(221 citation statements)
references
References 47 publications
(44 reference statements)
4
205
0
9
Order By: Relevance
“…Similar findings have been previously reported in children with type 1 diabetes mellitus; endothelial dysfunction was reported in the absence of structural atherosclerotic changes (37). Previous studies in various populations have shown that endothelial dysfunction is detected long before the angiographic appearance of atherosclerosis on the vessel wall (22) and has been reported to predict the progression of carotid IMT (38). It could be speculated that JIA may be primarily associated with endothelial dysfunction, apparent even at ages 7-10 years, independently of the presence of systemic or nonsystemic disease.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings have been previously reported in children with type 1 diabetes mellitus; endothelial dysfunction was reported in the absence of structural atherosclerotic changes (37). Previous studies in various populations have shown that endothelial dysfunction is detected long before the angiographic appearance of atherosclerosis on the vessel wall (22) and has been reported to predict the progression of carotid IMT (38). It could be speculated that JIA may be primarily associated with endothelial dysfunction, apparent even at ages 7-10 years, independently of the presence of systemic or nonsystemic disease.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, FMD was reported to show an inverse association with the index of small artery elasticity in both diabetic and healthy subjects, but not with IMT 26) . Recently, Halcox et al reported that FMD failed to show any significant association with carotid IMT at baseline but that it predicted annual progression of carotid IMT at the 6-year follow-up of 213 non-smoking middle-aged participants who did not initially have clinical CVD and diabetes 27) . In our study, FMD did not show any significant association with IMT, but showed a close association with stiffness parameter β, which is a functional index of the artery.…”
Section: Relationship Of Fmd/nmd Imt and Stiffness Parameter β Withmentioning
confidence: 99%
“…Furthermore, endothelial dysfunction predicts progression of atherosclerosis and incidence of cardiovascular events (46,47). Furthermore, endothelial dysfunction is reversed by a number of interventions proven to reduce cardiovascular risk, such as lipidlowering therapy, angiotensin-converting inhibitors, smoking cessation, and weight loss (44).…”
Section: Epidemiologymentioning
confidence: 99%